One Fish Two Fish Red Fish Blue Fish - Dr Seuss (HarperCollins Children's Books, 2011)
If you have yet to discover this hilarious tale of opposites, colours, numbers and nonsense, then you're in for a treat!
Keywords: Juvenile literature-Fiction